Fragments of asthenosphere incorporated in the lithospheric mantle underneath the Subei Basin, eastern China: Constraints from geothermobarometric results and water contents of peridotite xenoliths in Cenozoic basalts. Issue 1 (15th June 2019) - Hao, Yan-Tao; Bonadiman, Costanza; Coltorti, Massimo; Xia, Qun-Ke
Graphical abstract: Highlights: The Lianshan peridotite xenoliths are grouped base on clinopyroxene modal contents. The H2 O contents of clinopyroxene are lower than those theoretically expected. The water depletion result from diffusion during the chemical-physical readjustment. Abstract: Anhydrous, medium/coarse-grained spinel bearing mantle xenoliths from the Subei Basin, Eastern China have mineral arrangements that reflect low energy geometry. Because of clinopyroxene modal contents, they are grouped into cpx-rich lherzolites (cpx ≥ 14percentage), lherzolites (8 < cpx < 14%), cpx-poor lherzolites (6 < cpx ≤ 8%) and harzburgites (cpx up to 4%), without relevant textural differences from the most fertile to the most depleted lithotypes. The cpx-rich lherzolites have mineral chemistry close in composition to Primitive Mantle (PM), whereas cpx-poor lherzolite (and lherzolite) and harzburgite groups cannot be considered as a result of direct melting of the PM source. In addition, the high LREE, Th and U contents, coupled with a Sr enrichment of clinopyroxenes in these lithotypes, indicate the circulation of a silicate melt (with crustal components) in a variably depleted mantle sector well before the entrapment of the xenoliths by the host basalt. Despite the large differences in refractory lithophile element contents (i.e. Ca, Al and REE), the equilibrium temperatures never exceed 1021 °C with a constant difference (<200 °C) from harzburgites to cpx-rich lherzolites. Measured mineral water contents indicate that the whole rock contains, on average, 19 ± 7 ppm of H2 O without any systematic variation among rock types nor correlation with Al2 O3, light-REE and Yb (or Y) contents of cpx. The cpx H2 O contents of cpx-rich lherzolites (41–96 ppm) are, on average, one order of magnitude lower than those theoretically expected (214–530 ppm) for a residuum after a maximum of 3% of PM fractional (≈ bulk) melting in the spinel stability field. The proposed dehydration model suggests that the cold highly refractory harzburgites and cpx-poor lherzolites (and lherzolites?) may represent old cratonic lithospheric mantle modified at depth by the interaction with silicate melts, which may also have involved crustal components. In turn, cpx-rich lherzolites constitute fragments of upwelling fertile asthenosphere, which caused the removal/erosion of the lowermost part of the lithospheric mantle. This asthenosphere portion may have been incorporated in the lithospheric region since the Jurassic and it may have progressively cooled down after one (or more) partial melting episodes. The water depletion can be accounted for a continuous loss by diffusion during the subsolidus chemical-physical readjustment, well after (>5My, based on modelled H2 O solid-solid diffusion rate) the occurrence of the last melting episode.